EFEKTIVITAS EKSTRAK BUAH LADA HITAM (PIPER NIGRUM L) KOMBINASI JAHE MERAH (ZINGIBER OFFICINALE) UNTUK MENGOBATI PENYAKIT VITILIGO - Nasihah, Mima; Fajrin, Fitriana Ikhtiarinawati (Universitas Nahdlatul Ulama Sidoarjo, 2019)
Vitiligo is a disease that causes skin color fading caused by cells that form melanin can not function. The initial symptom is the appearance of white patches that will gradually become brighter and wider. Black pepper, aside from being used as a complement to cooking spices, its piperin content can stimulate the formation of skin melanin. Red Ginger is also believed to heal bad cells in the skin or restore damaged skin naturally, eliminating vitiligo because it contains collagen. This research using the experimental method. Data collection includes pH test, organoleptic test, cream effectiveness test and pharmaceutical test. Data analysis used the Anova One Way to find out whether differences cream composition affected color, texture, thickness, fondness. Test of T-Paired to determine differences vitiligo exposure before and after treatment. Comparison of Black Pepper: Red Ginger: Emulgade is (1:2:1), (1:1:1), (1:1:2), (1:1:3), (1:3:8). Anova One Way test results show that F count to cream color (24,718)> F table (4.53), F count to cream texture (11,834)>F table (4.53), F count to cream density (15,001)>F table (4.53) and F count to cream fondness (6,517)>F table (4.53). This shows that there is a significant difference the combination of red ginger black pepper cream on color, texture, density and fondness on the cream.Test the effectiveness cream use T-paired test with result T count (5.277)>T Table (2.131), showed that there was a significant difference in the vitiligo exposure before and after being given a cream of black pepper and red ginger. Pharmaceutical test explains that cream are homogeneous, semi-solid, has a distinctive odor, brownish yellow color, pH 6 and has a spread capacity of 5.2 cm.